Community and School-Based Surveys of Soil-Transmitted Helminth Infections on Samosir Island, Indonesia - Purba, Ivan Elisabeth; Girsang, Vierto Irennius; Amila, Amila; Harianja, Ester Saripati; Purba, Yunita; Wandra, Toni; Budke, Christine M. (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Soil-transmitted helminth (STH) infections are common in tropical and sub-tropical regions where they can have substantial local public health impacts. This study aimed to evaluate the prevalence of STH infection in the community and children aged 6 to 11 years attending government-run schools in the Simanindo sub-district of Samosir Island. In total, 314 individuals in the community and 187 children aged 6 to 11 years attending government schools were invited to provide a fecal sample. All fecal samples were examined microscopically using the Kato-Katz technique. The prevalence of STH infection in the community was 46.8% (147/314). Infections were caused by Ascaris lumbricoides (n=52), followed by Trichuris trichiura (n=48), and hookworms (n=26). The prevalence of STH infection in school-age children was 4.8% in 2023. All infections in this cohort were due to T. trichiura. Even though the MDA program effectively controls A. lumbricoides and hookworm infections in school children, the problem of controlling T. trichiura infection remains. Therefore, selective treatment after fecal sample examination is needed to prevent T. trichiura infection and the potential for infection-associated anemia. Health education focusing on personal hygiene and environmental sanitation is still important for preventing STH infections. The suggestion is a new community-based survey with random sampling is necessary to ensure the present prevalence of STH in the community.